2018
DOI: 10.1016/j.ijnss.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of happiness among Iranian nurses

Abstract: Objectives This study aimed to assess happiness and its predictors among a group of Iranian hospital nurses. Methods This cross-sectional study was done in 2016 on 620 hospital nurses who worked in five teaching hospitals affiliated to Kashan University of Medical Sciences, Kashan, Iran. Nurses were recruited through the census method. Data collection instruments were a researcher-made demographic and occupational characteristics questionnaire, the Oxford Happiness Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 24 publications
9
34
2
7
Order By: Relevance
“…Additionally, this study findings of associations of marital status, clinical rank and source of stress with GWB differed from those of Meng et al and Khosrojerdi et al (Khosrojerdi et al, ; Meng, Luo, Liu, Hu, & Yu, ). Meng et al reported that the both negative and positive emotions, satisfaction with life and relationships among nursing colleagues were associated with GWB, and Khosroderdi et al found that satisfaction with mental health, salary, quality of life, ward situation, working hours and behaviours of doctors was associated with GWB (Khosrojerdi et al, ; Meng et al, ). A study by Kahneman et al revealed that a higher monthly income allowed greater family welfare and quality of life, resulting in better work performance due to greater GWB (Kahneman & Deaton, ).…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Additionally, this study findings of associations of marital status, clinical rank and source of stress with GWB differed from those of Meng et al and Khosrojerdi et al (Khosrojerdi et al, ; Meng, Luo, Liu, Hu, & Yu, ). Meng et al reported that the both negative and positive emotions, satisfaction with life and relationships among nursing colleagues were associated with GWB, and Khosroderdi et al found that satisfaction with mental health, salary, quality of life, ward situation, working hours and behaviours of doctors was associated with GWB (Khosrojerdi et al, ; Meng et al, ). A study by Kahneman et al revealed that a higher monthly income allowed greater family welfare and quality of life, resulting in better work performance due to greater GWB (Kahneman & Deaton, ).…”
Section: Discussioncontrasting
confidence: 93%
“…The nurses in China who participated in this study had lower GWB scores (61.67 ± 18.11 for male nurses and 59.38 ± 14.32 for female nurses) than the general Chinese population (76.30 ± 9.48), whereas Khosrojerdi et al found that nurses in Iran had an average score of 123.4 ± 18.4, which was higher than that of their general population (Khosrojerdi et al, ). Additionally, this study findings of associations of marital status, clinical rank and source of stress with GWB differed from those of Meng et al and Khosrojerdi et al (Khosrojerdi et al, ; Meng, Luo, Liu, Hu, & Yu, ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations